Far from equilibrium field theory for strongly coupled light and matter: Dynamics of frustrated multimode cavity QED - Hossein Hosseinabadi; Darrick E. Chang; Jamir Marino (Physical Review Research)
Light-matter interfaces have now entered a new stage marked by the ability to engineer quantum correlated states under driven-dissipative conditions. To propel this new generation of experiments, we are confronted with the need to model nonunitary many-body dynamics in strongly coupled regimes by transcending traditional approaches in quantum optics. In this work, we contribute to this program by adapting a functional-integral technique, conventionally employed in high-energy physics, in order to obtain nonequilibrium dynamics for interacting light-matter systems. Our approach is grounded in constructing “two-particle irreducible” (2PI) effective actions, which provide a nonperturbative and conserving framework for describing quantum evolution at a polynomial cost in time. We apply our method to complement the analysis of spin-glass formation in the context of frustrated multimode cavity quantum electrodynamics, initiated in our accompanying work [Hosseinabadi et al., Phys. Rev. Res. 6, 043313 (2024)10.1103/PhysRevResearch.6.043313]. Finally, we outline the capability of the technique to describe other near-term platforms in many-body quantum optics, and its potential to make predictions for this new class of experiments.